A community based cross - sectional study on types of domestic accidents and their treatment seeking behaviour - B. V., Divya; T. M., Jayasree; J. W., Felix A. (International Journal Of Community Medicine And Public Health, 2016)
Background: The present study was done to find out different types of domestic accidents, their relationship and the treatment seeking behaviour of the respondents. The survey focused on the types of domestic accidents such as falls, burns, scalds, electrical trauma, injury and accidental poisoning and their relationship with age, sex, time, place, site of injury and their treatment seeking behavior. Methods: The study was carried out from April 2010 to August 2010 in Chidambaram town. Among 50,000 populations, 33 wards were used for training and teaching medical students, interns and post graduates. In this study cluster sampling technique was used and sample of 300 households were surveyed for the details of types and relationship of domestic accidents, with a pretested structured proforma. Results: The majority of the accidents seen in our study were scalds (36%), followed by falls (31.1%), injury due to sharp objects (24.2%) and total number of accidents was found in 103 individuals. It was observed that the commonest place of accident for electrical trauma and accidental poisoning was living room, common place for falls were staircase and other space around home. Majority of accidents occurred in the kitchen (63.1%) followed by other space around home (22.4%) which occurred during 8-12 noon (32%). The most common reason for falls were old age, hyperactive children and debilitated patients. Depression was the leading cause for poisoning in adults. Conclusions: Hospital based data may incompletely reflect the occurrence of injury in the population as many injured patients might not seek or manage to obtain hospital care. Hence community based studies which are done for larger populations are always helpful to the policy makers to enforce laws and recommendations to the community.